Female Subordination in Pornographic - Zhang, Yi (Chaturbhujeshwar Academic Journal, 2024)
This study examines female subordination in pornographic films through “bodily power,” a concept that evolved from Foucault and Butler. Pornographic films, now commercial visual products, shape societal views on sex, gender, and more. The paper analyzes films using textual data for interpretation. It reveals the construction of subjectivity and cognition by presenting bodily experiences within power dynamics, interpreted through post-structural and feminist lenses. It uncovers the alienation of women’s bodies, hidden exploitation mechanisms, and the secretive construction of subordination. Pornographic films objectify women, making their bodies consumable commodities to fulfill male centric fantasies, supported by a patriarchal culture of false desire, reinforcing the objectification of bodies. This work reveals and explains reality, which others do not perceive easily, and the social constructs hidden within it. In addition, this work prompts a critical reevaluation of gender domination and broader socio-economic discussions.